Respuesta :
midpoint = ((x1 + x2)/2) , ((y1 + y2)/2)
midpoint = ((3 + -5)/2) , ((-1 + -3)/2)
midpoint = (-2/2) , (-4/2)
midpoint = -1 , -2
midpoint = ((3 + -5)/2) , ((-1 + -3)/2)
midpoint = (-2/2) , (-4/2)
midpoint = -1 , -2
There are midpoint formulas, one for the x-coordinate of the midpoint and another for the y-coordinate:
x1+x2
xm = -----------
2
and
y1+y2
ym = ----------
2
Note that when you ad y1 and y2 together and divide this sum by 2, you get the average, or midpoint, of the y-distance separating the two points.
Here the two points are (3,-1) and (-5,-3).
The x-coord. of the midpoint is xm = (3 + [-5])/2, or 8/2, or 4.
The y-coord is ym = (-1+[--3])/2, or -4/2, or -2.
Thus, the midpoint of the line segment joining (3,-1) and (-5,-3) is (4,-2).
x1+x2
xm = -----------
2
and
y1+y2
ym = ----------
2
Note that when you ad y1 and y2 together and divide this sum by 2, you get the average, or midpoint, of the y-distance separating the two points.
Here the two points are (3,-1) and (-5,-3).
The x-coord. of the midpoint is xm = (3 + [-5])/2, or 8/2, or 4.
The y-coord is ym = (-1+[--3])/2, or -4/2, or -2.
Thus, the midpoint of the line segment joining (3,-1) and (-5,-3) is (4,-2).